The role of supplementary cementitious materials in mitigating concrete's carbon emissions through life cycle assessment - Dawood, Dawood S.; Abu Bakar, Nabilah; Alias, Aidi Hizami; Safiee, Nor Azizi; Mohd Nasir, Noor Azline; Sharaai, Amir Hamzah (Springer Science and Business Media, 2026)
Concrete production remains a major source of CO2 emissions, yet Malaysia lacks accurate, up-to-date, and locally derived emission factors for concrete raw materials, particularly when SCMs are incorporated. This absence of localized data undermines the reliability of environmental assessments and limits the adoption of low-carbon concrete. Therefore, this study aims to establish a comprehensive, Malaysia-specific CO2 inventory for concrete constituents and evaluate the environmental benefits of SCM-based concrete mixes. A hybrid cradle-to-gate life cycle assessment (LCA), combining process-based modeling with selected input–output emission factors, was performed for cement, aggregates, water, superplasticizer (SP), fly ash (FA), silica fume (SF), and ground-granulated blast furnace slag (GGBS). These material-level results were then used to calculate the CO2 emissions of conventional and SCM-modified concrete through an extensive parametric analysis. Cement exhibited an emission factor of 917 g CO2/kg, while SP recorded the highest value at 2640 g CO2/kg. The binder dominated concrete emissions, contributing 71–95% of total CO2. Conventional mixes produced 435–497 kg CO2/m3, whereas SCM-based concretes achieved reductions of up to 61%, especially when high GGBS contents were combined with moderate FA or SF. These mixes also maintained or improved compressive strength compared to control concrete. This study provides the first detailed, localized CO2 inventory for concrete materials in Malaysia and demonstrates the effectiveness of optimized SCM combinations for significant carbon reduction. Future research should integrate cost, durability, multi-objective optimization, and cradle-to-grave boundaries to support national low-carbon construction strategies.